2010
DOI: 10.1136/adc.2010.188433
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal lidocaine and midazolam for procedural sedation in children

Abstract: This study has shown that the combined use of lidocaine spray and atomised INM appears to be a safe and effective method to achieve short-term sedation in children to facilitate medical care and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 27 publications
0
56
2
4
Order By: Relevance
“…6 One method of preventing nasal irritation is to administer intranasal lidocaine 60 seconds before midazolam using a mucosal atomization device. Chiaretti and colleagues 18 found a single 10-mg dose of atomized lidocaine prior to a 0.2 to 0.5 mg/kg dose of intranasal midazolam to be effective at reducing nasal irritation, but the children in this study were given midazolam for conscious sedation rather than for seizures. This may be a viable option in the future if development of a premixed lidocaine/midazolam solution is feasible, but the delay in midazolam administration that would occur from giving lidocaine first is not ideal and could lead to patient harm.…”
Section: Safetymentioning
confidence: 79%
“…6 One method of preventing nasal irritation is to administer intranasal lidocaine 60 seconds before midazolam using a mucosal atomization device. Chiaretti and colleagues 18 found a single 10-mg dose of atomized lidocaine prior to a 0.2 to 0.5 mg/kg dose of intranasal midazolam to be effective at reducing nasal irritation, but the children in this study were given midazolam for conscious sedation rather than for seizures. This may be a viable option in the future if development of a premixed lidocaine/midazolam solution is feasible, but the delay in midazolam administration that would occur from giving lidocaine first is not ideal and could lead to patient harm.…”
Section: Safetymentioning
confidence: 79%
“…A notable downside to intranasal delivery is the potential for nasal mucosal irritation, which would likely be more poorly tolerated in neonates than in adults. It has been suggested that lidocaine could be coadministered with any intranasal drugs in neonates and children to help mitigate this issue [119].…”
Section: Intranasalmentioning
confidence: 99%
“…Intranasal citrate has been used as a model for intranasal midazolam in volunteers, predosing the nares with lidocaine, or mixing lidocaine with the citrate to reduce the discomfort [16]. Nasal pre-dosing with lidocaine has been shown to reduce the discomfort [34], although lidocaine itself gives a rather unpleasant taste.…”
Section: Buccal Sedationmentioning
confidence: 99%